Translational Dysregulation in Cancer: Molecular Insights and Potential Clinical Applications in Biomarker Development - Vaklavas, Christos; Blume, Scott W.; Grizzle, William E. (Frontiers in Oncology, 2017)
Although transcript levels have been traditionally used as a surrogate measure of gene expression, it is increasingly recognized that the latter is extensively and dynamically modulated at the level of translation (mRNA to protein). Over the recent years significant progress has been made in dissecting the complex post-transcriptional mechanisms that regulate gene expression. This advancement in knowledge came hand in hand with the progress made in the methodologies to study translation both at gene-specific as well as global genomic level. The majority of translational control is exerted at the level of initiation; nonetheless protein synthesis can be modulated at the level of translation elongation, termination, and recycling. Sequence and structural elements and epitranscriptomic modifications of individual transcripts allow for dynamic gene-specific modulation of translation. Cancer cells usurp the regulatory mechanisms that govern translation to carry out translational programs that lead to the phenotypic hallmarks of cancer. Translation is a critical nexus in neoplastic transformation. Multiple oncogenes and signaling pathways that are activated, upregulated, or mutated in cancer converge on translation and their transformative impact “bottlenecks” at the level of translation. Moreover, this translational dysregulation allows cancer cells to adapt to a diverse array of stresses associated with a hostile microenviroment and antitumor therapies. All elements involved in the process of translation, from the transcriptional template, the components of the translational machinery, to the proteins that interact with the transcriptome, have been found to be qualitatively and/or quantitatively perturbed in cancer. This Review discusses the regulatory mechanisms that govern translation in normal cells and how translation becomes dysregulated in cancer leading to the phenotypic hallmarks of malignancy. We also discuss how dysregulated mediators or components of translation can be utilized as biomarkers with potential diagnostic, prognostic, or predictive significance. Such biomarkers have the potential advantage of uniform applicability in the face of inherent tumor heterogeneity and DNA instability. As translation becomes increasingly recognized as a process gone awry in cancer and agents are developed to target it, the utility and significance of these potential biomarkers is expected to increase.